Penerapan Antarmuka Transmisi Data EKG Berbasis Komunikasi BLE (Bluetooth Low Energy) Pada Mobile Middleware - Yugi Trilia Septiana; Eko Sakti Pramukantoro; Rakhmadhany Primananda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
In 2016, the first cause of death in the world was heart disease. It happened because heart disease was often detected late. Internet of Health Things (IoHT) is one of the technological developments of the IoT that can be used as a solution to the problem of electrocardiogram monitoring (ECG). The system consists of AD8232 ECG sensor that connected to an ESP32 sensor that has a BLE module to send the data that was obtained from sensor ECG to mobile middleware. BLE is one of the data transmission media that has advantages in the use of low power, low radiation that make the BLE is suitable to be used in human body. BLE is one of Low-Power Wide-Area-Network (LP-WAN) protocol that makes BLE suitable to be used in IoT environment. This research resulted in a measurement of the performance of the ESP32 BLE sensor node that is capable of processing and sending ECG data to mobile middleware with a delay of 4.02 seconds. So, the results didn't fulfill the requirements in ECG data transmission which is 4 seconds maximum for monitoring uses delay.